Uji Daya Hambat Ekstrak Etanol Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) terhadap Bakteri Staphylococcus aureus - Susi Novaryatiin; Ahmad Ramli; Syahrida Dian Ardhany (Jurnal Surya Medika (JSM), 2019)
Dayak Onion is a typical plant of Central Kalimantan. This plant has been traditionally used by the Dayak community as traditional medicine. Empirically, Dayak Onion bulbs are known to have properties to treat boils or skin diseases. The purpose of this study was to determine the ability of inhibition of Dayak Onion ethanol extract in inhibiting Staphylococcus aureus bacteria and to determine the effectiveness of the inhibition of Dayak Onion ethanol extract and concentration that could inhibit the growth of Staphylococcus aureus bacteria. This research was carried out by testing the antibacterial activity of Dayak Onion extract at levels of 1%, 5%, 10%, and 15% using the Disc Diffusion (Kirby-Bauer) method by using disc paper. The results showed that Dayak Onion ethanol extract was able to inhibit the growth of Staphylococcus aureus and effectively inhibited the growth of Staphylococcus aureus at concentrations of 1%, 5%, 10%, and 15% with inhibitory zones of 14.3 ± 2.5 mm ; 16.6 ± 1.7 mm; 16.2 ± 2.0 mm; and 18.0 ± 1.7 mm.